International seminar on nuclear war and planetary emergencies : (World Scientific, 2004)
Water - Pollution, Biotechnology - Transgenic Plant Vaccine, Energy, Black Sea Pollution, AIDS - Mother-Infant HIV Transmission, Transmissible Spongiform Encephalopathy, Limits of Development - Megacities, Missile Proliferation and Defense - Information Security, Cosmic Objects, Desertification, Carbon Sequestration and Sustainability, Climatic Changes, Global Monitoring of Planet, Mathematics and Democracy, Science and Journalism, Permanent Monitoring Panel Reports, Water for Megacities Workshop, Black Sea Workshop, Transgenic Plants Workshop, Research Resources Workshop, Mother-Infant HIV Transmission Workshop, Sequestration and Desertification Workshop, Focus Africa Workshop